2019
DOI: 10.3126/jaim.v8i2.28002
|View full text |Cite
|
Sign up to set email alerts
|

Complications and predictors of diagnostic yield of endobronchial forceps biopsy in visible lesions

Abstract: Background: Fiberoptic bronchoscopy is an important and relatively safe procedure for evaluation of various pulmonary diseases. Endobronchial forceps biopsy is commonly performed sampling technique for visible lesions in tracheobronchial tree. Diagnostic yield of biopsy depends upon lesion type and the number of biopsy samples taken. This study aimed to evaluate the complications and diagnostic yield of endobronchial forceps biopsy in visible lesions and correlate the number of biopsy samples taken with the yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…The diagnostic yield of the EBB varies from 48 to 93%. 8 The overall diagnostic yield was 68.4% which is similar to the study by Shrestha BK et al 14 and Rivera MP et al 15 but it is lower than the study by Zavala DC 16 and Popp W et al 17 British Thoracic Society guidelines recommends diagnostic level of 85% should be attainable when definite endobronchial tumor is visible. In the current study, the diagnostic yield of EBB was 75% despite repeated biopsies were taken in 21.2% of cases, which is below the recommended level.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The diagnostic yield of the EBB varies from 48 to 93%. 8 The overall diagnostic yield was 68.4% which is similar to the study by Shrestha BK et al 14 and Rivera MP et al 15 but it is lower than the study by Zavala DC 16 and Popp W et al 17 British Thoracic Society guidelines recommends diagnostic level of 85% should be attainable when definite endobronchial tumor is visible. In the current study, the diagnostic yield of EBB was 75% despite repeated biopsies were taken in 21.2% of cases, which is below the recommended level.…”
Section: Discussionsupporting
confidence: 69%
“…Shrestha BK et al 14 reported mild bleeding of 9.9% in recent study, which may be higher due to EBB. The transient hypoxemia was seen in 18.4% and most of them did not require any specific intervention as stated by Jones A.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…We had previously reported our experience in a small cross sectional study where the results were similar. 10 The limitation of the study is its retrospective nature and relatively small sample size.…”
Section: Discussionmentioning
confidence: 99%